2016
DOI: 10.1186/s12879-016-2088-8
|View full text |Cite
|
Sign up to set email alerts
|

What are the factors associated with human immunodeficiency virus/sexually transmitted infection screening behaviour among heterosexual men patronising entertainment establishments who engaged in casual or paid sex? – Results from a cross-sectional survey in an Asian urban setting

Abstract: BackgroundLate presentation of human immunodeficiency virus (HIV) is associated with heterosexual transmission, particularly among heterosexual men in Asia. Although data on HIV/sexually transmitted infection (STI) testing behaviour is increasing, information is still lacking among heterosexual men who receive far lesser attention and are generally invisible in HIV/ STI prevention, particularly in the Asian urban setting. The aim of this study was to assess the prevalence of HIV/STI testing among heterosexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…MSW preferred testing in private health facilities whereas FSW preferred public health facilities. Among MSW, HIV non-testing was associated with higher education, poor self-efficacy, and poor testing norms and perceptions.Our finding that only 50% of MSW reported testing for HIV in the last 12 months is similar to prior studies from Asia(30)(31)(32). A study of heterosexual MSW in Singapore found that only 27% had tested for HIV or STIs in the past 6 months(30).…”
supporting
confidence: 89%
“…MSW preferred testing in private health facilities whereas FSW preferred public health facilities. Among MSW, HIV non-testing was associated with higher education, poor self-efficacy, and poor testing norms and perceptions.Our finding that only 50% of MSW reported testing for HIV in the last 12 months is similar to prior studies from Asia(30)(31)(32). A study of heterosexual MSW in Singapore found that only 27% had tested for HIV or STIs in the past 6 months(30).…”
supporting
confidence: 89%
“…We found that 50% of HMSW reported not testing for HIV in the past 12 months. Non-testing for HIV was common in prior studies from Asia and Africa [ 34 36 ]. A study of HMSW in Singapore found that only 27% had tested for HIV or STIs in the past 6 months [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-testing for HIV was common in prior studies from Asia and Africa [ 34 36 ]. A study of HMSW in Singapore found that only 27% had tested for HIV or STIs in the past 6 months [ 34 ]. In China, only 48.6% of MSW who have sex with men had tested for HIV [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure , a substantial proportion still present with late stage infections. Underlying reasons include reluctance to test due to stigma and discrimination, lack of awareness of testing benefits, low risk perception of HIV exposure and fear of undesirable socio‐economic consequences . Late presentation was previously also associated with sociodemographic factors such as older age, singlehood and working in non‐professional occupations .…”
Section: Discussionmentioning
confidence: 99%